The risk of low energy availability among athlete females in Saudi Arabia: a cross-sectional study - Khatib, Mai A.; Aljaaly, Elham A.; Hafiz, Maryam S.; Alamri, Alkhuzama; Alzahrani, Wejdan (Frontiers in Public Health, 2024)
Introduction Low energy availability (LEA) is a state of inadequate energy reserves that results from a negative energy balance. This condition can lead to severe health risks such as amenorrhea and osteoporosis. Various causes for LEA, such as eating disorders and exercise addiction, have been reported in the literature. However, data in Saudi Arabia are lacking. This cross-sectional study measures the prevalence of LEA, eating disorders, and exercise addiction among adult females in Saudi Arabia and identifies possible associated risk factors. Methods The sample comprised 119 female athletes who filled out an online survey adapted from the LEA in Females Questionnaire, the Eating Disorder Examination Questionnaire, and the Exercise Addiction Inventory. Results Participants showed a high prevalence of LEA (66.4%), eating disorder (33.6%), and exercise addiction (10.1%), confirming the association between normal weight and LEA in females living in Saudi Arabia (p < 0.00). Discussion and conclusion With an increasing number of females in the country interested in following a healthy lifestyle, there is a need to raise the awareness of the population on the issues of LEA, eating disorders, and exercise addiction and their effects on the body by developing educational programs about energy intake and healthy physical activity routines.